Report on the 13th conference on "Strategies for Survival: collections, data, institutions" of the Groupe des Cartothécaires de LIBER, 3-7 September, Helsinki, Finland. - Fleet, Christopher (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
In spite of being an inauspicious 13th conference, this was a successful and highly enjoyable gathering of map curators, which - despite a close encounter with a Helsinki tram! - managed to avoid any mishaps or disasters. Our Finnish Organising Committee provided a well-organised, interesting programme with considerable good-humour and kindness, allowing an excellent base for our discussions and talks. As usual there was a varied spread of people, issues and subjects brought together, both practical and theoretical, historical and contemporary, reflecting the diverse nature of European map libraries. This report is a somewhat personal and abbreviated account of the conference, summarising the main issues of the various papers, providing an introduction to them, and highlighting general trends. Eight of the papers are being published in this issue of the LIBER Quarterly.